Water Use in Florida - Tatiana Borisova; Roy R. Carriker (EDIS, 2009)
FE797, a 4-page illustrated fact sheet by Tatiana Borisova and Roy R. Carriker, summarizes the USGS estimates of Florida water withdrawals and water use in several categories: agricultural irrigation, public supply, power generation, commercial use, recreational irrigation, and domestic self-supplied. Includes references. Published by the UF Department of Food and Resource Economics, April 2009.